THE EFFECTS OF WORK STRESS AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT THE SECRETARIAT OF THE GENERAL ELECTION COMMISSION (KPU) OF BANDAR LAMPUNG CITY - Br.Ginting, Jessica Maheratiarna; Atika, Dewie Brima; Apandi, Apandi (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2024)
Employee performance is the result of carrying out the tasks assigned to employees but many organizations require employees to further improve their abilities and skills at work (Hasibuan, 2013). Wirawan (2009) explained various factors influencing the decline in employee performance such as work stress and job satisfaction. Employees who feel satisfied with their work tend to be more productive, while those who do not feel satisfied tend to have low productivity. Employee performance will improve if employees are satisfied with their jobs because their needs and expectations have been met. Work stress and job satisfaction play an important role in influencing employee performance. This study used a quantitative method and data were collected by distributing questionnaires. The population in this study was all employees at the Secretariat of the General Election Commission (KPU) of Bandar Lampung City with a total of 30 people. Determination of the sample used a saturated sampling technique so the entire population was used as the sample. Validity, reliability, normality, multicollinearity, and heteroscedasticity tests were conducted to ensure data quality. The results of the study indicate that work stress has a negative effect on employee performance, while job satisfaction has a positive effect on employee performance. Based on the t-test, the work stress variable has a significance value of 0.000 < 0.05, and the job satisfaction variable has a significance value of 0.001 < 0.05, indicating that both variables significantly affect employee performance. The coefficient of determination test (R2) obtains a value of 78.3 meaning that work stress and job satisfaction contribute 78,3% of the influence on employee performance.